BARGAINING GAME AND EQUITY SHARING SYSTEM IN EMPLOYMENT PROBLEM - Anton Abdulbasah Kamil (Proceedings of ICMSA, 2005)
Profit sharing has been proposed as a solution to underemploymentresulting from collective bargaining, but the empirical results areambiguous and the theoretical basis for this claim is weak. This papershows equity sharing can, in theory, solve the principle shortcomings ofprofit sharing. First, equity sharing can resolve both underemployment andover employment. Second, the results do not depend on assuming thatinsiders and the firm are prevented from bargaining over employmentlevel. Third the system does not require government intervention sinceboth sides can benefit from adopting equity sharing.Keywords: Bargaining game, profit sharing model, equity sharing.